Osteological development of the Channichthyidae (Teleostei: Notothenioidei) ... - Voskoboinikova, Olga S. (Société Française d'Ichtyologie, 1997)
The osteological development of eight species (Champsocephalus gunnari Loennberg 1905, Channichthys rhinoceratus Richardson 1844, Pseudochaenichthys georgianus Norman 1937, Pagetopsis macropterus (Boulenger 1907), Chionodraco rastrospinosus DeWitt & Hureau 1979, Chaenodraco wilsoni Regan 1914, Chaenocephalus aceratus (Loennberg 1906) and Cryodraco antarcticus Dollo 1900) of the most advanced among the notothenioid family Channichthyidae was examined. All the studied channichthyids in general show a sequence in the formation of bones similar to the sequence found in the most advanced nototheniids (Pleuragramma antarcticum (Boulenger)) and bathydraconids (Parachaenichthys). Morphogenesis of the skeleton of the channichthyids is the slowest one within all the notothenioids, that is probably the manifestation of a paedomorph evolution of the suborder Notothenioi-dei. Within channichthyids, the rate of the osteological development also becomes slower along the line ...